Pengembangan Metode Pembelajaran Matematika Berdasarkan Diagnosis Kesulitan Belajar Siswa SLTP - Masbah Masbah; Hamzah Hamzah (Universitas Negeri Malang, 2016)
The study was conducted to explore difficulties faced by students in learning Linear and Nonlinear Equation with Two Variables, and to develop a method to solve the difficulties. It applied a classroom action research (CAR) approach in a secondary school (SLTP). The subjects were second graders of (SLTP) Sungguminasa, Gowa, South Sulawesi. Some mathematics teachers were involved as collaborators and participants in this study. Data were collected by questionnaires and tests in every cycle after giving remedial teaching. A descriptive statistics was used to analyze data. The results showed that the average score of students using lecture method, discussion method, and assignment method was increased